The relationship between postpartum levator ani muscle avulsion and signs and symptoms of pelvic floor dysfunction. (19th February 2014) - van Delft, K; Sultan, AH; Thakar, R; Schwertner‐Tiepelmann, N; Kluivers, K
<x xml:space="preserve">Abstract</x> Objective To establish the relationship between postpartum levator ani muscle (LAM) avulsion and signs and/or symptoms of pelvic floor dysfunction (PFD). Design Observational longitudinal cohort study. Setting District General University Hospital, UK. Population or sample Primigravida at 36 weeks' gestation and 3 months postpartum. Methods Pelvic floor muscle strength (PFMS) and pelvic organ prolapse were assessed clinically using validated methods. Transperineal ultrasound was performed to identify LAM avulsion and measure hiatus dimensions. Validated questionnaires evaluated sexual function, urinary and faecal incontinence. Main outcome measures PFD signs and symptoms related to LAM avulsion. Results Two hundred and sixty nine primigravida without LAM avulsion participated and 71% (n = 191) returned postpartum. LAM avulsion was found in 21% of vaginal deliveries (n = 30, 95%CI 15.1–28.4%). Women with minor and major avulsion had worse PFMS (P < 0.038) and more anterior compartment prolapse (maximum stage 2; P < 0.024). Antenatal hiatus antero‐posterior diameter on ultrasound was significantly smaller in women sustaining avulsion (P = 0.011). Postnatal measurements were significantly increased following avulsion. Women with major avulsion were less sexually active at both antenatal and postnatal periods (P < 0.030). These women had more postnatal urinary incontinence and symptoms such as reduced vaginal sensation and 'too loose vagina'. No postnatal differences were found for faecal incontinence, prolapse symptoms or quality of life. The correlation of differences in variables was only slight–fair with avulsion severity. Conclusions Twenty one percent of women sustain LAM avulsion during their first vaginal delivery with significant impact on signs and symptoms of PFD. As avulsion has been described as the missing link in the development of prolapse; longer term follow‐up is vital.